Turning to the Visitor's Body: Affective Exhibition and the Limits of Representation - Harris, Jennifer (UNESCO- ICOFOM, 2012)
As museums have found themselves needing to express concepts and events for which we seem not to have an adequate verbal language, they have begun to turn to the physical body of the visitor in order to find a way to express the inexpressible and to represent the unrepresentable. Affect, physical bodily sensations that precede emotional understanding are being foregrounded in museum exhibition. Unsettling, unpredictable visceral responses are being provoked as some museums seem to be saying that conventional object-based exhibitions seem exhausted. Examination of three museum spaces that operate entirely on the affective level is used to demonstrate the emerging role of affect as a key museum tool. Affect centres the visitor in the exhibition resulting in the greatest power in the museum that the visitor has ever had.